Perspectives on expert generalist practice among Japanese family doctor educators: a qualitative study. Issue 3 (June 2021) - Kaneko, Makoto; Oishi, Ai; Sawa, Noriaki; Irving, Greg; Fujinuma, Yasuki
No abstract available